Extreme, expedition, and wilderness medicine. Issue 10012 (19th December 2015) - Imray, Christopher H E; Grocott, Michael P W; Wilson, Mark H; Hughes, Amy; Auerbach, Paul S
Summary: Extreme, expedition, and wilderness medicine are modern and rapidly evolving specialties that address the spirit of adventure and exploration. The relevance of and interest in these specialties are changing rapidly to match the underlying activities, which include global exploration, adventure travel, and military deployments. Extreme, expedition, and wilderness medicine share themes of providing best available medical care in the outdoors, especially in austere or remote settings. Early clinical and logistics decision making can often have important effects on subsequent outcomes. There are lessons to be learned from out-of-hospital care, military medicine, humanitarian medicine, and disaster medicine that can inform in-hospital medicine, and vice-versa. The future of extreme, expedition, and wilderness medicine will be defined by both recipients and practitioners, and empirical observations will be transformed by evidence-based practice.